MENGANTISIPASI PASAR TERBUKA DENGAN MENCIPTAKAN KEUNGGULAN BERSAING MELALUI PENDEKATAN STRATEGI PEMASARAN (Pendekatan Marketing Mix dalam Prespektif Islam) - Tamamudin (Jurnal Hukum Islam, 2012)
Islam has economic and business systems that are well defined and have proven their efficacy and strength. In marketing practices, Islamic teachings embedded in the Quran, Hadits of the Prophet (pbuh), Ijma’ (consensus), and Qiyas (analogy) have a foundation that is based on equity and justice. This paper attempts to identify the main characteristics of the Islamic perspective on the framework of marketing mix. The paper analyses the four pillars of marketing mix which are product, price, promotion, place and people. The paper adopts the methodology of evaluating the prevailing practices of marketing mix from an Islamic perspective with the sole aim to highlight the efficacy and strength of an Islamic ethical framework. Finally, the paper illustrates that Islam provides a framework for the creating and sustaining of a strong ethical marketing culture.